Transesterification of Used Cooking Oil Using CaO/MCM-41 Catalyst Synthesized from Lapindo Mud by Sonochemical Method - Ida Bagus Putra Mahardika; Wega Trisunaryanti; Triyono Triyono; Dwi Putra Wijaya; Kumala Dewi (Indonesian Journal of Chemistry, 2017)
Transesterification of waste cooking oil using CaO/MCM-41 synthesized from Lapindo mud by the sonochemical method has been carried out. The silica was separated from the mud by reflux method used 6 M HCl and 6 M NaOH. The silica was then analyzed by XRF and used as silica source in MCM-41 synthesis. The synthesis of MCM-41 was carried out by the sonochemical method, then analyzed by XRD, Infrared spectrophotometer, SAA, and TEM. The Ca2+ was loaded onto the MCM-41 by wet impregnation method under variation of the Ca2+ content of 1.15, 1.29, 2.39, and 3.25 wt.% analyzed by ICP produced CaO(1), CaO(2), CaO(3), and CaO(4)/MCM-41 catalyst respectively. Transesterification of used cooking oil was carried out under methanol/oil mole ratio of 15/1, the temperature of 55, 65 and 75 °C, and catalyst/oil weight ratio of 5/100, 10/100 and 15/100 for 2 h by reflux method. The XRD analysis of the MCM-41 showed a characteristic peak at 2θ = 2-5°. The MCM-41 has a specific surface area of 1290 m2/g and pore diameter of 3.4 nm. The TEM images of MCM-41 showed ordered pore distribution with a hexagonal shape. The highest conversion of methyl ester was 78.17 wt.% obtained under the reaction conditions at 65 °C and catalyst/oil weight ratio of 15/100 using the CaO(4)/MCM-41. The lifetime CaO(4)/MCM-41 catalyst was 9.8 h.